Fattening Pigs with Tannin-Rich Source (Ceratonia siliqua L.) and High Doses of Vitamin E: Effects on Growth Performance, Economics, Digestibility, Physiology, and Behaviour - Bottegal, Diego Nicolas; Latorre, María Ángeles; Lobón Ascaso, Sandra; Verdú, Marçal; Álvarez-Rodríguez, Javier (MDPI, 2025)
This study aimed to assess the impact on growth, economic results, apparent nutrient digestibility (CTTAD), physiological variables, and animal behaviour when 214 fattening pigs (78 ± 8.5 kg of initial body weight and 130 ± 4.5 days of age) of both sexes (gilts and boars) were fed two levels of carob pulp (Cp, 0 vs. 20%) and two doses of vitamin E (Vit E, 30 vs. 300 IU/kg) for 40 days. No interaction effects between factors studied (Cp, Vit E, and sex) were observed on the variables. Most productive traits were unaffected by Cp or Vit E inclusion. However, the Cp increased the feed conversion ratio during the first 20 days. The Cp group showed a higher CTTAD of ether extract and hemicellulose but lower CTTAD of crude protein. Pigs fed Cp had a lower plasmatic urea content than the control group. The high Vit E doses increased the CTTAD of every nutrient and the plasmatic α-tocopherol content. The pigs fed Cp tended to spend more time eating in the early morning, likely to mitigate tannins’ astringent effects. Dietary inclusion of 20% Cp in finishing high-conformation pigs is possible without affecting overall performance though it reduces nutrient CTTAD and increases feeding cost. Supra-nutritional doses of Vit E do not affect pig performance but increase the α-tocopherol deposition with potential antioxidant effects.